2011
DOI: 10.1590/s1984-46702011000100021
|View full text |Cite
|
Sign up to set email alerts
|

An unusual reproductive mode in Hypsiboas (Anura: Hylidae)

Abstract: We report an unusual reproductive behavior of Hypsiboas pardalis (Spix, 1824). Species belonging to this genus usually are known to reproduce in lentic water bodies, with the development of exotrophic tadpoles. Herein, the bromeligenous behavior is reported for the first time in Hypsiboas Wagler, 1830. Although this reproductive behavior has been observed more than once here, we believe that it is not typical of Hypsiboas, being better characterized as an unusual reproductive mode for Hypsiboas, indicating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…191.0 and 191.2); further, several studies have demonstrated that the same species can display behavioural plasticity with respect to reproductive modes (e.g. Dendropsophus ebraccatus , Boana pardalis (Hylidae), Physalaemus spiniger (Leptodactylidae); Haddad and Pombal, ; Haddad and Prado, ; Touchon and Warkentin, ; Moura et al., ; Toledo et al., ) and that the existence of alternative reproductive strategies might have evolved either due to trait selection in order to maximize fitness and avoid predation and competition or in relation to specific environmental conditions (e.g. Magnusson and Hero, ; Haddad and Prado, ; Taborsky et al., ; Taborsky and Brockmann, ).…”
Section: Discussionmentioning
confidence: 99%
“…191.0 and 191.2); further, several studies have demonstrated that the same species can display behavioural plasticity with respect to reproductive modes (e.g. Dendropsophus ebraccatus , Boana pardalis (Hylidae), Physalaemus spiniger (Leptodactylidae); Haddad and Pombal, ; Haddad and Prado, ; Touchon and Warkentin, ; Moura et al., ; Toledo et al., ) and that the existence of alternative reproductive strategies might have evolved either due to trait selection in order to maximize fitness and avoid predation and competition or in relation to specific environmental conditions (e.g. Magnusson and Hero, ; Haddad and Prado, ; Taborsky et al., ; Taborsky and Brockmann, ).…”
Section: Discussionmentioning
confidence: 99%
“…The use of bromeliads as vocalization sites is known for several species of other genera within Cophomantini (see [ 89 93 ]), including other species of Bokermannohyla [ 33 , 44 , 94 ]. However, the use of bromeliads for breeding (spawning and development of tadpoles) has been recorded only for Boana pardalis , although it was interpreted as a case of behavioral plasticity in relation to its most common reproductive mode ( i .…”
Section: Discussionmentioning
confidence: 99%
“…This set of circumstances has shaped the evolution of 'be prepared' strategies [5], involving the coevolution of maternal oviposition behaviour (e.g. selection of protected sites) [6][7][8] with egg morphology and physiology (e.g. colour, patterning, temperature/desiccation tolerance).…”
Section: Introductionmentioning
confidence: 99%